Predictive clinical features and outcomes of vitrectomy for proliferative diabetic retinopathy. Issue 3 (26th February 2008) - Yorston, D; Wickham, L; Benson, S; Bunce, C; Sheard, R; Charteris, D
Abstract : Objective: To study the preoperative characteristics, complications and outcomes of vitrectomy for proliferative diabetic retinopathy and to identify any factors that may predict visual outcome. Methods: Prospective study of 174 consecutive vitrectomies in 148 patients, with a minimum follow-up of 4 months. Results: 41 (27.7%) patients had a vision of <6/60 in their better eye at presentation. Posterior retinal breaks occurred in 47 (27.0%) eyes. Postoperative complications included vitreous cavity haemorrhage in 37 (22.0%) eyes, retinal detachment in five eyes (3.0%), and rubeotic glaucoma in five eyes (3.0%). 124 (74.7%) eyes improved by at least 0.3 LogMAR units, and 15 (9.0%) worsened by at least 0.3 LogMAR units. 119 (71.7%) eyes had a visual acuity of 6/60 or better, and 27 (16.3%) were counting fingers or worse. Only 16 (11.1%) patients had a vision of <6/60 in both eyes at latest follow-up. Preoperative vision in both the operated eye and the contralateral eye, macular detachment, and long-acting intraocular tamponade were independent predictors of poor postoperative vision, but this model accounted for only a small proportion of the observed variation in outcomes. Conclusions: Major complications are rare after vitrectomy for proliferative diabetic retinopathy, and >70% of eyes will regain vision of 6/60 or better. Visual outcomes remain unpredictable.